Estrategias de marketing mix para la comercialización local de ropa para bailarines producida en Quito - Cevallos Paz, Sofía Pilar (2010)
The general objective of the investigation of this thesis work is to determine the most suitable marketing mix strategies for the local sale of dancing apparel produced in Quito. In order to develop the objective mentioned before, the route to follow was to trace specific objectives which lead to the progress of the work and are cited below. • Understand what is dance, know what is the necessary dothing to practice this discipline. What are the uses that dancers give to their dothing. Leam the process for the making of this type of dothes. The evolution of this art and the present demand by the dancers for this kind of apparel • Identity and analyze the supply of the dothing used for dancing that exists actually in Quito. The distribution channels, promotion, the suppliers, costs and prices, substitutes and the consumer's behavior • Outline the marketing mix strategies to introduce the dancing dothes to Quito's market. The method used for the investigation was the backing in various tools such as interviews, focus groups, written and phone investigations due to the fact that the necessity of information about dancer's behaviors as consumers which did not exist was present. Other secondary sources such as books and intemet were also used. In Quito, there are only two stores that offer these types of products. Due to the absence of supply for these articles, we have some consequences. The economic situation of the dancers does not let them buy the product if there is a variation on the plice. For this reason, due to the necessity of this artists, independent seamstresses have become the principal rivals of the two stores that supply this dothing: Adagio and Capezio. This thesis contains a substantial analysis of the present demand, high plices, costs of production, reduced supply, and the high taxes for the importing of this types of garments wanted by the dancers because at the same time they have generated a valuable market. The marketing mix strategies (product, plice, distribution and promotion) that should be applied to succeed in the local sales of clothes for dancers produced in Quito are delived from the investigation carried out.